Pendidikan Islam dan Iman Kepada Malaikat: Strategi Pembentukan Aqidah di Era Global - Hasibuan, Louisa Anwar; Soraya, Anis; Aisyah, Rahma Nur; Hamda, Mutiara; Rosyidah, Nur; Wismanto, Wismanto (STAI Denpasar Bali, 2024)
The main problem in this study is what and how the concept of educational values ​​contained in faith in angels. To answer this question, data were collected from the Qur'an and Sunnah, primary and secondary reference books that discuss the concept of faith, especially faith in metaphysics, and the concept of the purpose of Islamic education. The purpose of this study is to reveal the Strategy for Establishing Faith in the Global Era around faith in angels. In this discussion, the author uses descriptive and logical analysis methods. In order for the problem to be solved more easily, the main problem above is detailed in two sub-problems, namely: 1). What is the relationship between education and faith, especially faith with metaphysics, 2). How is the concept of educational values ​​that are contained in faith in angels. After collecting data from various sources above, the author analyzed and found a relationship and influence between the influence of education and faith, and found educational values ​​that could be described from aspects of faith to metaphysics, in this case faith in angels which is part of the strategy of forming aqidah in the global era full of challenges. This aspect provides an influence on the soul and experience of students and in this case the concept of values ​​can be applied in the world of Islamic education.